The Association Between the Sedative Loads and Clinical Severity Indicators in the First-Onset Major Depressive Disorder - Wang, Yen-Chin; Lin, Hai-Ti; Lu, Mong-Liang; Huang, Ming-Chyi; Chen, Chun-Hsin; Wu, Tzu-Hua; Wang, Sabrina; Mao, Wei-Chung; Kuo, Po-Hsiu; Chen, Hsi-Chung (Frontiers in Psychiatry, 2019)
Background: High sedative use in a major depressive episode may imply specific clinical features. This study aims to examine the correlation between sedative use and clinical severity indicators in the initial treatment phase of first-onset major depressive disorder. Methods: A study cohort in the first episode of major depressive disorder was used to conduct pharmacological dissection. All participants had at least a 2-year follow-up period with a complete treatment record. The daily defined dose of antidepressants and augmentation agents were calculated as the antidepressant load and augmentation load, respectively. Sedative use, which was calculated as the equivalent dosage of lorazepam, were defined as the sedative load. These psychotropic loads were measured monthly and the averaged psychotropic loads for 24 months were obtained. Results: A total of 106 individuals (75.5% female) were included. The mean duration of disease course in participants was 5.5±3.5 years. In the multiple regression analysis, after controlling for other classes of psychotropics and comorbid anxiety disorders, the sedative load independently correlated with higher number of antidepressants used, higher number of antidepressant used with an adequate dose and duration, more psychiatric emergency and outpatient visits within 2 years of disease onset. Conclusion: High loading of sedatives correlated with several indicators of clinical severity in major depressive disorder. The sedative load may be used as a specifier to identify subgroups in patients with major depressive disorder.